(untitled) (Journal of Parents and Teachers, 2026)
Interesting realities such as the number of nomads travelling around Europe, gypsies, transients, people who have no fixed abode. On the other hand, the 1992 National Conference of Music Educators gives us some ideas for giving music a more central role in schools. In addition, the new Dictionary of the Royal Academy contains more than 12,000 new entries, definitions or meanings, bringing the total number of words to 85,000.